Soil stabilizer and soil desertification treatment method

By using soil stabilizers composed of calcium polyvinylate and other materials, the problem of decreasing water absorption and water retention in high-salt environments is solved, and the stability and permeability of the soil are significantly improved, which is suitable for the treatment of desertified soil.

CN119614208APending Publication Date: 2025-03-14SICHUAN GELAN ENVIRONMENTAL ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411675492.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Sodium polyacrylate degrades slowly in the natural environment and is difficult to be degraded by microorganisms. Its water absorption and water retention are significantly reduced in high-salt environments, resulting in poor soil sandification treatment effect.

Method used

Calcium polyvinylate is used as the main component of soil stabilizer, and combined with bentonite, potassium methyl silicate and composite silicate cement and other materials, a new soil stabilizer is formed. Through the high water absorption and water retention of calcium polyvinylate, the soil permeability coefficient is reduced and the soil's compressive and shear strength is improved.

Benefits of technology

It significantly improves the compressive, shear strength and permeability of the soil, reduces soil loss, has good soil moisturizing function, is suitable for high-salt environments, and calcium polyvinylate can naturally degrade and will not cause long-term pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614208A_ABST
    Figure CN119614208A_ABST
Patent Text Reader

Abstract

The invention provides a soil stabilizer and a soil desertification control method, and belongs to the field of soil desertification control, the soil stabilizer comprises the following components by mass: 70-90% of a base material; 7-15.2% of a water retention material; 3-14.8% of a curing material; wherein the water retention material comprises polyethylene acid calcium; sodium polyacrylate is replaced with polyethylene acid calcium, the polyethylene acid calcium is good in natural degradability, degradation products are free of pollution, the polyethylene acid calcium is suitable for the high-salt environment of desertified soil, the overall stability of sandy soil is enhanced, the mechanical properties of compression resistance and shear strength are improved, and soil loss is reduced; and the soil conditioner has a good soil moisturizing function, is more beneficial to plant growth, improves the evaporation resistance or impermeability of sandy soil, prevents leakage of surface water or underground water, and stores water resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil desertification control, and in particular to a soil stabilizer and a soil desertification control method. Background Art

[0002] At present, the main means to improve desertification is to plant trees and grass. However, long-term wind erosion and water erosion make the soil structure loose, and nutrients are lost in large quantities, resulting in a decrease in soil fertility, exposed plant roots, low survival rate, and difficult growth of trees and grass, which ultimately leads to land desertification and ecological environment deterioration. Therefore, to improve soil desertification, we must first improve the soil. Soil solidification, soil and water moisture retention, and water resource storage play a very positive role in its management.

[0003] In the state of soil sandification, the permeability coefficient of sand is about 1×10 -2 ~3×10 -5 cm / s, loose soil structure, fast water seepage, no moisture retention and other factors are not conducive to plant growth and ecological environment protection. my country has started research on soil desertification control very early, and many institutions and technicians have been developing products that can be used to stabilize soil, moisturize soil or better store water resources as anti-seepage materials. Chinese patent CN116584198B discloses a soil improvement method to prevent soil acidification, alkalization and desertification, using a modifier composed of desulfurized gypsum, sodium polyacrylate microspheres coated with potassium bicarbonate and ammonium bicarbonate aqueous solution, and zeolite adsorbed with aluminum hydroxide hydrosol to improve soil desertification. However, the degradation rate of sodium polyacrylate in the natural environment is slow, and it is difficult to be degraded by microorganisms. Long-term and large-scale use will have adverse effects on the soil environment. At the same time, one of the important reasons for soil desertification is the serious degree of soil salinization, and sodium polyacrylate is sensitive to salt, especially in a high-salt environment, its water absorption and water retention will be significantly reduced. Summary of the invention

[0004] In view of this, the present invention proposes a soil stabilizer and a soil desertification control method to solve the problem that sodium polyacrylate degrades slowly in the natural environment and is difficult to be degraded by microorganisms, and that the water absorption and water retention of sodium polyacrylate are significantly reduced in a high-salt environment.

[0005] The technical solution of the present invention is achieved as follows: The present invention provides a soil stabilizer comprising the following components in percentage by mass:

[0006] Base material 70-90%,

[0007] Water retaining material 7~15.2%,

[0008] Curing material 3~14.8%,

[0009] Among them, the water-retaining material includes calcium polyacrylate. Calcium polyacrylate is a polyacrylic acid (PAA) in which part or all of the carboxyl groups (-COOH) are combined with calcium ions (Ca 2+ ) cross-linked salt. Its structure can be expressed as [-CH2-CH(COOH)-] n Ca. It is a white or light yellow powdery substance at room temperature. It is insoluble in water, but can absorb water to form a gel. It can exist stably under acidic and neutral conditions, but it will decompose under strong alkaline conditions. Since soil is a porous medium composed of three phases, its pores are interconnected in space; water passes through the pores and capillaries of the soil body and causes evaporation or leakage and loss, so it is necessary to greatly reduce the permeability coefficient of the soil, fill the pores inside the soil body as much as possible, and use highly absorbent substances to retain water in the pores to form pore water, thereby achieving the purpose of soil water conservation. This application uses calcium polyvinyl acid as a water-absorbing substance, and its water absorption and water retention performance is comparable to that of sodium polyacrylate (see Table 1), but calcium polyvinyl acid can be gradually degraded under natural conditions and will not cause long-term pollution to the environment. At the same time, soil desertification mostly occurs in the arid and rainless areas in the north. The soil environment in this area is usually neutral or slightly alkaline. After completing the long-term water absorption and water retention function, calcium polyvinyl acid can slowly degrade into calcium salts and other non-polluting substances in a slightly alkaline soil environment. Moreover, sodium polyacrylate is sensitive to salt, especially in a high-salt environment, its water absorption and water retention will decrease significantly, which is an obvious disadvantage of its application in saline-alkali land or high-salt environment; while calcium polyacrylic acid has good salt tolerance and will not be adversely affected by the salt content of the environment. This application is used as a soil stabilizer, using local natural sand as the base material and other components as admixtures. Compared with no admixtures added, the compressive strength and shear strength of the soil can be increased by about several times; the anti-seepage performance is increased by about 1,000 times or more, and it has a very strong anti-seepage effect (see Table 1).

[0010] On the basis of the above technical solution, preferably, the water-retaining material further includes potassium methyl silicate and bentonite, and the weight percentage of each component of the water-retaining material is:

[0011] Calcium polyacrylate: 1-3.1%,

[0012] Potassium methyl silicate: 0~0.1%,

[0013] Bentonite: 6-12%.

[0014] More preferably, the solid content molecular weight of calcium polyacrylic acid is ≥30 million, the molecular weight of low polymer with a degree of polymerization below 1000 is ≤5%, and the residual monomer is ≤0.48%.

[0015] It is further preferred that the solid content of potassium methyl silicate is ≥85%, and the content of active silicone therein is ≥18%. Potassium methyl silicate is an organosilicon waterproofing agent, a new type of building waterproofing material, with good permeability and crystallinity. The silanol groups (silicone) in its molecular structure react with the silanol groups in the silicate material to dehydrate and crosslink, thereby realizing the "reverse capillary effect" to form an excellent hydrophobic layer, and at the same time has the functions of micro-expansion and increasing density. Adding potassium methyl silicate to sand has excellent waterproofing effect and the advantages of anti-seepage, moisture-proof, and anti-aging, and reduces peeling caused by freezing, thawing and weathering. The effect is long-lasting and resistant to high and low temperatures (-50 to 150°C).

[0016] More preferably, the bentonite is sodium bentonite in powder form with a purity of ≥95% and a particle size of ≤1.0 mm.

[0017] More preferably, the substrate is natural sand, which includes natural clay, natural sand, a mixture of sand and clay, or mineral sand. The organic matter content of natural sand is ≤1.5%, the sand particle size is ≤5mm, and the water content is 0-10%. The sand particle size distribution should meet the requirements of good grading according to the actual needs of the use scenario.

[0018] More preferably, the curing material comprises the following components in percentage by mass:

[0019] Composite silicate cement: 1-6%,

[0020] Slaked lime powder: 1~3.5%,

[0021] Microsilica fume: 1-4.5%,

[0022] Short fiber: 0~0.8%.

[0023] Bentonite and microsilica powder are both of large specific surface area, filling the pores between particles in sand and soil, improving density, and significantly improving the strength and bearing capacity of the sand-soil mixture; bentonite is used in sand-soil bonding, has high plasticity and strong bonding force, and has stable physical and chemical properties under high temperature conditions. The regular relationship between bentonite content and the permeability coefficient of the finished product can be seen in Figure 1 The higher the bentonite content, the smaller the soil permeability coefficient; microsilica fume has an effect of about 5 times that of cement, which can reduce costs and improve durability. More than 80% of microsilica fume has a fineness of less than 1μm and a density of 2.3-2.6g / cm 3, SiO2 content>99%, whiteness between 70-94 degrees, Mohs hardness of 7, dry mixing method is used for mixing for at least 50 to 60 seconds; slaked lime is a better cementitious material, and its hydration product forms a crystalline gel to fill the gaps in the sand, thereby improving the compactness and strength of the sand. Slaked lime powder is usually in powder form. When preparing stabilizer products, first-class or superior slaked lime powder is preferably used, with a fineness of 325 mesh, a content greater than 90%, a free water content of 0.4-2%, a qualified volume stability, and a sieve residue of ≤5%; short fibers are added to the product admixture so that under the adhesion of the gel, it helps to improve the shear strength of this product. Under the high adsorption and strong bonding force of gel substances such as calcium polyacrylic acid, bentonite, composite silicate cement, etc., the gel substances block the capillary channels inside the sand, effectively improve the capillary structure of minerals such as clay and sand, increase the internal friction angle and cohesion of the sand, and improve the mechanical properties and stability of the sand, which not only significantly improves the soil's compressive and shear strength, but also significantly improves the soil's anti-permeability performance. In addition, the mixing water is not measured here, and only the final total moisture content of the product is considered to be no more than 20%. The mixing water can be drinking water, surface water and groundwater, with a pH of 6.0 to 11.0. Other water quality requirements should meet the standard requirements for plain concrete water in the "Concrete Mixing Water Standard JGJ63-89".

[0024] More preferably, the short fibers include at least one of basalt fibers, glass fibers, synthetic organic fibers and plant fibers, the short fibers have a diameter of 66 to 248 μm, and a single fiber length of 3 to 15 mm.

[0025] Further preferably, the composite silicate cement is mixed with gypsum and aluminosilicate polymer, and the strength of the solidified material is not less than PC42.5; the content of magnesium oxide and magnesium oxide in the cement is ≤5.0%, the content of sulfur trioxide is ≤3.5%, the fineness is 80μm, the residue on the square hole sieve is ≤10%, and other requirements meet the inspection standards of ordinary silicate cement.

[0026] On the other hand, the present invention also provides a method for controlling soil desertification, using the above-mentioned soil stabilizer, comprising the following steps: Step 1, determining the mass percentage of each component of the soil stabilizer according to the control environment requirements and preparing the materials. Among them, in industrial production, a continuous neutralization reactor or a spray drying device is often used to achieve large-scale and efficient production of calcium polyvinyl acid; in addition, a polyvinyl acid solution can be mixed with a calcium salt (such as calcium chloride, calcium nitrate, etc.) solution for neutralization reaction to generate a calcium polyvinyl acid precipitate, which is then filtered, washed and dried to obtain the calcium polyvinyl acid precipitate; the chemical equation for preparing calcium polyvinyl acid by copolymerization of ethylene acid and calcium salt is as follows,

[0027] nCH2=CHCOOH→(CH2-CHCOOH) n ,

[0028] 2(CH2-CHCOOH) n +Ca(OH)2→(CH2-CHCOO) n Ca + 2H2O,

[0029] Among them, (CH2-CHCOO) n Ca stands for calcium polyacrylate.

[0030] Step 2: Mix natural sand, bentonite, slaked lime powder, microsilica powder, short fibers, calcium polyacrylate, potassium methyl silicate and composite silicate cement in the above proportions and mix them evenly; Step 3: Spray water to stir the mixture, and transport the mixture to the construction site for paving and rolling, with a compaction degree of not less than 85%, to form an impermeable layer with a thickness of not less than 4 cm. The present invention is a product that uses on-site sand as the base material, which can quickly and efficiently stabilize the sand, retain moisture and improve the soil, which is more conducive to plant growth; the 4 cm thick impermeable layer can significantly reduce its permeability coefficient to 5×10 -9 cm / s or less, so that the overall soil anti-seepage performance is good to meet the requirements of industry standards. Laying the anti-seepage layer on the surface of the sandy soil layer can quickly stabilize the sand and prevent excessive evaporation of underground water; laying the anti-seepage layer at a certain depth underground can prevent groundwater or surface water from leaking and losing. In addition, this product can also be used as a roadbed isolation layer to prevent groundwater from damaging the roadbed. Therefore, the application areas involve desertification control and roadbed anti-seepage isolation layers, as well as the laying of anti-seepage layers in rivers, reservoirs, and aquatic farms, with a wide range of application scenarios.

[0031] The soil stabilizer and soil desertification control method of the present invention have the following beneficial effects compared with the prior art:

[0032] (1) The present invention adopts calcium polyacrylic acid to replace sodium polyacrylate, which has good natural degradability, and its degradation products are pollution-free. It is suitable for the high-salt environment of desertified soil, which not only enhances the overall stability of sandy soil, improves the mechanical properties of compressive strength and shear strength, and reduces soil loss; it also has a good soil moisture retention function, which is more conducive to plant growth, improves the anti-evaporation or anti-seepage performance of sandy soil, prevents surface water or groundwater from leaking, and saves water resources; and forms an isolation layer in the soil to resist the damage of groundwater to the roadbed; the cost is low, because local materials are used to save resources and reduce long-distance transportation costs; the preparation is simple, and conventional mechanical equipment can meet the construction requirements; it can be recycled, and conventional building materials are used, which is environmentally friendly and harmless.

[0033] (2) The present invention forms a three-dimensional molecular structure in the soil through the synergistic effect of calcium polyacrylic acid and potassium methyl silicate. Calcium polyacrylic acid absorbs and locks pore water in the soil pores through its high water accumulation and water retention capacity, thereby filling the soil micropores, thereby achieving a significant improvement in the soil's compressive strength and water retention capacity while reducing the soil permeability coefficient.

[0034] (3) The present invention studies and tests the synergistic effect of calcium polyacrylate and potassium methyl silicate and finds that when the content of calcium polyacrylate varies within the range of 1.5 to 2.5%, it has a greater impact on the reduction of the permeability coefficient of the product, and a higher content of potassium methyl silicate has a very obvious effect on reducing the permeability coefficient of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 is a curve diagram reflecting the relationship between bentonite content and permeability coefficient of the present invention; DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] A soil stabilizer of the present invention comprises the following components by mass:

[0040] Natural sand: 8100g. Natural sand is taken from local sand, which is a mixture of natural clay, natural sand, and sand and clay. The organic matter content is 1.3%; the diameter of the sand is ≤5mm, the particle size distribution should meet the local environmental requirements, and the water content is 7%.

[0041] Bentonite: 800 g, the purity of sodium bentonite is 98%, and the particle size is less than 1.0 mm.

[0042] Slaked lime powder: 200g, first-class quality, fineness of 325 mesh and content of 95%, free water content of 1.3%, volume stability is qualified, and the sieved residue is ≤5%.

[0043] Microsilica powder: 300g, more than 80% of which is less than 1μm, and the density is 2.3-2.6g / cm 3 The SiO2 content is 99.7%, the whiteness is between 70-94 degrees, and the Mohs hardness is 7.

[0044] Short fiber: 50g, a mixture of basalt fiber and glass fiber, with a diameter of 66 to 248μm and a single fiber length of 3 to 15mm.

[0045] Calcium polyacrylate: 100g, solid content molecular weight> 30 million, low polymer with degree of polymerization below 1000 ≤5%, residual monomer ≤0.48%, impurity sulfate (as SO4) ≤0.5%, loss on drying ≤10%, residue on ignition ≤75%, heavy metal (as Pb) ≤0.002%, arsenic (as As2O3) ≤0.0002%.

[0046] Potassium methyl silicate: 5g, solid content>85%, silicone content (active matter content)>18%.

[0047] Composite Portland cement: 400g, strength PC42.5; magnesium oxide, magnesium oxide content is 4.5%, sulfur trioxide content is 3%, fineness is 80μm, square hole sieve residue ≤10%; other requirements meet the inspection standards of ordinary Portland cement.

[0048] Mixing water: 900mL, use external canal water, pH 6.0-11.0. Other water quality requirements should comply with the standard requirements for plain concrete water in "Concrete Mixing Water Standard JGJ63-89".

[0049] A soil desertification control method of the present invention adopts the soil stabilizer of this embodiment, comprising the following steps: step 1, preparing materials according to the mass of natural sand, bentonite, slaked lime powder, microsilica powder, short fibers, calcium polyacrylic acid, potassium methyl silicate and composite silicate cement in embodiment 1; step 2, mixing the above components evenly; step 3, spraying water to stir the mixture, and transporting the mixture to the construction site for paving and rolling, with a compaction degree of not less than 85%, to form an anti-seepage layer with a thickness of not less than 4 cm.

[0050] Among them, in Examples 1 to 5, the component ratio without adding potassium methyl silicate as an admixture is used as a comparative example. Taking Example 1 as an example, the mass of each component of Comparative Example 1 is natural sand: 8100g, bentonite: 800g, slaked lime powder: 200g, microsilica powder: 300g, short fiber: 50g, calcium polyacrylic acid: 100g, composite silicate cement: 400g, and mixing water: 900mL.

[0051] In Examples 1 to 10, the component ratios in which calcium polyacrylic acid and potassium methyl silicate are not added as admixtures are blank controls. Taking Example 1 as an example, the masses of the components of the blank control 1 are: natural sand: 8200 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, composite silicate cement: 400 g, and mixing water: 900 mL.

[0052] Example 2

[0053] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8080 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 120 g, potassium methyl silicate: 5 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0054] Example 3

[0055] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8050 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 150 g, potassium methyl silicate: 5 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0056] Example 4

[0057] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8000 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 200 g, potassium methyl silicate: 5 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0058] Example 5

[0059] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 7950 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 250 g, potassium methyl silicate: 5 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0060] Example 6

[0061] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 7890 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 310 g, potassium methyl silicate: 5 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0062] Among them, in Examples 6 to 10, the component ratio without adding calcium polyacrylic acid as an admixture is used as a comparative example. Taking Example 6 as an example, the mass of each component of Comparative Example 6 is natural sand: 8200g, bentonite: 800g, slaked lime powder: 200g, microsilica powder: 300g, short fiber: 50g, potassium methyl silicate: 5g, composite silicate cement: 400g, and mixing water: 900mL.

[0063] Example 7

[0064] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8000 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 200 g, potassium methyl silicate: 7 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0065] Example 8

[0066] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8000 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 200 g, potassium methyl silicate: 8 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0067] Example 9

[0068] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8000 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 200 g, potassium methyl silicate: 9 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0069] Example 10

[0070] A soil stabilizer of the present invention comprises the following components by mass: natural sand: 8000 g, bentonite: 800 g, slaked lime powder: 200 g, microsilica powder: 300 g, short fiber: 50 g, calcium polyacrylate: 200 g, potassium methyl silicate: 10 g, composite silicate cement: 400 g, and mixing water: 900 mL. The remaining requirements and implementation methods are the same as those in Example 1.

[0071] The finished products of Examples 1 to 10 were tested for anti-permeability coefficient and compressive strength. Among them, three methods were used to determine the permeability coefficient: 1) Rough observation test method: The test pit water seepage test method was used to test the permeability coefficient: the test method simulating the "test pit water seepage test principle" was used to place the experimental finished product in a PVC round tube with a diameter of about 100 mm and a length of about 50 cm, and then compacted to achieve a compaction degree of about 85%. The finished product was 4 cm thick, and the tube was filled with water. A calibration ruler was set inside the tube. The water level drop was measured every hour, accurate to 0.5 mm. Roughly calculate the permeability coefficient; 2) Accurate measurement: The permeability coefficient of the satisfactory formula experimental product was determined by the variable head permeability test method. The variable head permeameter is mainly used to determine the permeability coefficient of the relevant test product in the permeability test under the variable head. 3) Verify the permeability coefficient: Sampling and sending samples to a third-party qualified testing unit for measurement. The compressive strength performance of the product is tested by a confined compressive strength test. By drying the soil mixed with the soil text of the present application, after it fully absorbs water, it is dried and the difference in soil mass before and after drying is weighed to test the water retention performance of the soil.

[0072] Among them, in addition to preparing samples for testing according to the combination of Examples 1 to 10, comparative examples 1 to 5 are also prepared, and comparative examples 1 to 5 do not add potassium methyl silicate as an admixture compared to the combination of Examples 1 to 5 (the comparative example correspondingly increases the proportion of natural sand); at the same time, comparative examples 6 to 10 are also prepared, and comparative examples 6 to 10 do not add calcium polyvinyl acid as an admixture compared to the combination of Examples 6 to 10; blank groups 1 to 10 are also prepared, and blank groups 1 to 10 do not add calcium polyvinyl acid and potassium methyl silicate as admixtures compared to the combination of Examples 1 to 10, and the following Table 1 is obtained.

[0073] Table 1

[0074]

[0075] According to the test results in Table 1, by comparing the permeability coefficients of Examples 1 to 10 with the blank control, it can be found that the permeability coefficients of the products with calcium polyacrylate and potassium methyl silicate as admixtures are exponentially reduced compared with the products without calcium polyacrylate and potassium methyl silicate as admixtures.

[0076] By comparing the permeability coefficients of Examples 1 to 10 horizontally, it can be found that as the content of calcium polyvinyl acid increases, the permeability coefficient of the product gradually decreases; further observation shows that when the content of calcium polyvinyl acid is less than 1.5% (see Examples 1 and 2), the reduction in the permeability coefficient of the product is not obvious, when the content of calcium polyvinyl acid varies within the range of 1.5 to 2.5% (see Examples 3 to 5), the permeability coefficient of the product decreases significantly, and when the content of calcium polyvinyl acid exceeds 2.5% (see Example 6), the reduction in the permeability coefficient of the product tends to be gentle. At the same time, the high content of potassium methyl silicate has a very obvious effect on reducing the permeability coefficient of the product (see Examples 7 to 10).

[0077] Comparing the products of Examples 1 to 5 with the products without potassium methyl silicate as an admixture, it can be found that the permeability coefficient of the products changes exponentially, but the products without potassium methyl silicate as an admixture are still better than the blank control products; while comparing the products of Examples 6 to 10 with the products without calcium polyvinyl acid as an admixture, it can be found that the change in the permeability coefficient of the products is not obvious. Therefore, it can be inferred that the component that mainly reduces the permeability coefficient of the product is potassium methyl silicate, and calcium polyvinyl acid can synergize with potassium methyl silicate to play a certain effect of reducing the permeability coefficient, but the effect is not significant.

[0078] By comparing the compressive strength, shear strength and moisturizing function of Examples 1 to 10 horizontally, it can be found that the moisturizing ability of products with a higher calcium poly(poly(acrylic acid) acid content is significantly improved; the compressive strength and shear strength of products with a higher potassium methyl silicate content are significantly improved.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A soil stabilizer, characterized in that: Contains the following components in percentage by mass, Base material 70-90%; Water retaining material 7~15.2%; Solidified material 3-14.8%; Wherein, the water-retaining material comprises calcium polyacrylic acid.

2. A soil stabilizer according to claim 1, characterized in that: The water-retaining material also includes potassium methyl silicate and bentonite. The weight percentage of each component of the water-retaining material is: Calcium polyacrylate: 1-3.1%, Potassium methyl silicate: 0~0.1%, Bentonite: 6-12%.

3. A soil stabilizer according to claim 2, characterized in that: The solid content molecular weight of the calcium polyacrylic acid is ≥30 million, the molecular weight of the low polymer with a polymerization degree below 1000 is ≤5%, and the residual monomer is ≤0.48%.

4. A soil stabilizer according to claim 2, characterized in that: The solid content of the potassium methyl silicate is ≥85%, and the content of the active silicone therein is ≥18%.

5. A soil stabilizer according to claim 2, characterized in that: The bentonite is sodium-based bentonite with a purity of ≥95% and a particle size of ≤1.0 mm.

6. A soil stabilizer according to claim 2, characterized in that: The substrate is natural sand, which includes natural clay, natural sand, a mixture of sand and clay, or mineral sand. The organic matter content of the natural sand is ≤1.5%, the sand particle size is ≤5mm, and the water content is 0-10%.

7. A soil stabilizer according to claim 6, characterized in that: The solidified material comprises the following components in percentage by mass: Composite silicate cement: 1-6%, Slaked lime powder: 1~3.5%, Microsilica fume: 1-4.5%, Short fiber: 0~0.8%.

8. A soil stabilizer according to claim 7, characterized in that: The short fibers include at least one of basalt fibers, glass fibers, synthetic organic fibers and plant fibers. The short fibers have a diameter of 66 to 248 μm and a single fiber length of 3 to 15 mm.

9. A soil stabilizer according to claim 7, characterized in that: The composite silicate cement is mixed with gypsum and aluminosilicate polymer, so that the strength of the solidified material is not less than PC42.

5.

10. A method for controlling soil desertification, characterized in that: The soil stabilizer according to any one of claims 7 to 9 is used, comprising the following steps: Step 1: Determine the mass percentage of each component of the soil stabilizer according to the environmental treatment requirements and prepare the materials; Step 2, the natural sand, bentonite, slaked lime powder, microsilica powder, short fiber, calcium polyvinyl acid, potassium methyl silicate and composite silicate cement are mixed in the above proportions and uniformly mixed; Step three: Spray water to stir the mixture, and transport the mixture to the construction site for spreading and rolling. The compaction degree should be no less than 85%, forming an anti-seepage layer with a thickness of no less than 4 cm.

Citation Information

Patent Citations

  • Soil improvement method for preventing soil acidification, alkalization and sandification

    CN116584198B